Visual Performance of Adults With Prelingual Auditory Impairment - Rietveld, Simon; Spiering, Mark; Rotteveel, Mark; van Beest, Ilja (American annals of the deaf (Washington, D.C. 1886), 2004)
Reaction times and picture evaluations by 18 adults with hearing loss were compared with those of 18 matched controls during two visual priming tasks. In Task 1, participants reacted to sexual and plant target pictures (while influenced by similar preceding pictures) by pressing “sex” or “plant” buttons. In Task 2, they evaluated target Japanese ideographs (while influenced by preceding positive or negative facial expressions as prime pictures) by pressing “positive” or “negative” buttons. In Task 1, the controls had the faster responses. In Task 2, they showed the usual congruent priming effect during very short prime presentations. Participants with hearing loss showed this effect only during short and long prime presentation times; thus, they were not superior to the controls in picture recognition, instead showing (a) impaired processing of visual information or (b) impaired perceptual-motor skills regarding quick responses to visual information (or both).